Effects of a Portland cement additive rich in SiO2 and Al2O3 in microstructure densification of RAP incorporated RCCP mixes. (20th October 2020) - Debbarma, Solomon; Ransinchung R.N, G.D.; Dhaka, Manish
Highlights: Asphalt cohesion failure is associated with RAP-concrete. Higher dosage of additives rich in SiO2 and Al2 O3 could densify the microstructure of the RAP-concrete. Al2 O3 particles can provide a filler effect. RAP-concrete shows prominent effect in tensile stresses. Abstract: Past studies shows that the introduction of extra calcium silicate hydrate (C-S-H) gels, by means of various supplementary cementitious materials, did not show much significant effect on the strength of the roller compacted concrete pavement (RCCP) mixes made with reclaimed asphalt pavement (RAP) aggregates. Therefore, this paper is an attempt to refine the pores of RAP-RCCP mixes by inducing filler effect with the help of SiO2 and Al2 O3 particles, derived by means of a Portland cement additive. The incorporation levels of the additive were 0, 2, 4, 6, 8, and 10%, respectively, which were introduced into the RCCP mixture containing 50% RAP aggregates (R-50 mix). Based on the scanning electron microscope images, it was observed that the asphalt cohesion failure was prevalent although the additional calcium silicate hydrate gels were able to refine the microstructure of the mortar paste. However, improvement in the pore structure of the RAP-RCCP mixes was observed as the SiO2 content increases. Moreover, the presence of Al2 O3 particles could also react with the calcium carbonate present in the concrete (as shown by x-ray diffractometer patterns) to produce hemicarboaluminate and monocarboaluminate which could act as a filler and densify the interfacial transition zone of the RAP concrete. This promising effect was observed when the additive was utilized in a proportion of 10% wherein a marginal enhancement of 2–7% was observed in the compressive, flexural, and split tensile strength of the R-50 mix. In fact, the calcium aluminate hydrate phases formed on reaction between the Al2 O3 particles and the calcium hydroxide could also induce higher progression reaction within initial days itself. Meanwhile, the relationships established in the present study also indicated a strong relation co-exists between the compressive and flexural strength, and compressive strength and the abrasion resistance as well.